Analyzing Fdi Economic Effects and Determinants in See Economies: Comparative Approaches - Jelena Zvezdanovic (Naše gospodarstvo/Our economy, 2013)
Foreign direct investment (FDI) is one of the most important external sources of finan- cing of economic growth in developing and transition countries. Its increasing im- portance is reflected in implementing structural changes in production and exports in the beneficiary countries. As they are characterized by relative stability and lon- g-term nature, it is not surprising that the need to investigate the preconditions for attracting FDI has become a subject of discussion in many countries. The strong growth of FDI after World War II has led to extensive research on the determinants of this type of investment. The vast amount of theoretical and empirical studies on FDI highlight a long list of determinants that try to explain direct investment by mul- tinational companies in a particular location. This article provides a critical review of the research methods that have been applied in order to assess key determinants and effects of FDI inflow. The application of certain methods in the selected articles depends on the type and quality of data as well as its availability. Therefore, it is very difficult to decide which methods provide scientifically valid results.